Problem-based learning combined with realistic mathematics approach grade V elementary school - Salmia, Salmia; Sudarmin, Sudarmin; Mujahidah, Mujahidah (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2022)
The study aimed to determine student learning outcomes with problem-based learning through a realistic mathematical approach in mathematics subjects for class V students. This type of research was quasi-experimental because in this study, no specific treatment (treatment) was given, but only revealed the symptoms that had been reported. It existed at the time this research was conducted, so there was no direct control over the independent variables. Data collection methods used are learning outcomes tests and documentation. The data analysis technique is the first using a descriptive statistical approach and paired sample test. The results showed that learning mathematics using problem-based learning through a realistic mathematics approach obtained an average of 80.00 students' mathematics learning outcomes, with students in the medium category with a percentage of 100%. The average normalized gain of 0.29 was convection into high, medium, and low categories, so the average normalized gain of students was in the medium category. This means that problem-based learning combined with a realistic mathematical approach to learning outcomes for fifth-grade students is in the medium category. The significance value of Asiymp. Sig. (2-tailed) is 0.09, which is greater than 0.05. Then according to the basis of decision-making in the Kolmogorov-Smirnov normality test above, it can be concluded that the data are normally distributed. Thus, the assumptions or requirements for normality distributed data in the regression model have been met.